2018
DOI: 10.1037/pri0000070
|View full text |Cite
|
Sign up to set email alerts
|

Use of reflective journaling to understand decision making regarding two evidence-based psychotherapies for PTSD: Practice implications.

Abstract: As part of a longitudinal investigation on implementation of 2 evidence-based psychotherapies (EBPs) for posttraumatic stress disorder, psychotherapists from 38 Department of Veterans Affairs residential treatment programs across the United States were asked to complete reflective journals every 4 months for a 1-year time period in regard to their successes and challenges in using prolonged exposure and cognitive processing therapy. This paper provides content analysis on the reflective journals of 24 of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Five studies with three unique datasets that included 515 providers (265 psychologists, 138 social workers, 23 psychiatrists, 39 nurses, 2 counselors, 1 peer support worker, and 47 other) reported that limited generalizability and rigidity of PE and CPT treatment protocols were barriers to implementation primarily among veterans who experience PTSD (Cook et al, 2013(Cook et al, , 2018Finley et al, 2020;Marques et al, 2016;Simiola et al, 2019). Providers noted that: (a) clients often need more than just 12 sessions of CPT to see improvement; (b) rigidity of protocols does not allow for administration with clients with limited cognitive function, low education, or complex PTSD; (c) structured sessions and amount of homework were barriers; and (d) certain portions of the protocol often do not fit with their clientele.…”
Section: Subtheme 23 Beliefs About Efficacy Of Ebts Influence Their I...mentioning
confidence: 99%
“…Five studies with three unique datasets that included 515 providers (265 psychologists, 138 social workers, 23 psychiatrists, 39 nurses, 2 counselors, 1 peer support worker, and 47 other) reported that limited generalizability and rigidity of PE and CPT treatment protocols were barriers to implementation primarily among veterans who experience PTSD (Cook et al, 2013(Cook et al, , 2018Finley et al, 2020;Marques et al, 2016;Simiola et al, 2019). Providers noted that: (a) clients often need more than just 12 sessions of CPT to see improvement; (b) rigidity of protocols does not allow for administration with clients with limited cognitive function, low education, or complex PTSD; (c) structured sessions and amount of homework were barriers; and (d) certain portions of the protocol often do not fit with their clientele.…”
Section: Subtheme 23 Beliefs About Efficacy Of Ebts Influence Their I...mentioning
confidence: 99%
“…Research has demonstrated that therapists will contradict their training in exposure therapy by modifying evidence-based protocols in ways that are not supported by research because of evaluating the protocol as inadequate for unique patient characteristics. (Cook et al, 2018). Perhaps one of the best supervision approaches to this concern is MICHAEL, BLAKEY, SHERRILL, AND AOSVED experiencing first hand how exposure is adaptable and, in fact, often the only treatment many patients will need.…”
Section: Addressing Other Trainee Concerns In Supervisionmentioning
confidence: 99%
“…Clinicians may cite psychiatric comorbidity as a reason against delivering exposure, despite numerous studies demonstrating that comorbidities generally do not preclude benefit from exposure (Meyer et al, 2014). Clinicians and clinicians-in-training sometimes think their patients are the exception to empirical findings based on unique patient factors and that these factors the patient exhibits are rule-outs for offering exposure therapy (Cook, Simiola, McCarthy, Ellis, & Wiltsey Stirman, 2018; Feeny, Hembree, & Zoellner, 2003).…”
Section: Negative Beliefs and Attitudes About Exposure Therapymentioning
confidence: 99%
“…Reflective journaling has been used as an educational strategy in nursing and psychology 31 education programs to support the development of critical thinking and to enhance decisionmaking. Reflective journaling has been touted as an effective way for teachers to gather important information about the clinical application and decision-making process for frontline providers.…”
Section: Sp Encountermentioning
confidence: 99%
“…Reflective journaling has been touted as an effective way for teachers to gather important information about the clinical application and decision-making process for frontline providers. 31 Purposefully engaging in critical thinking dispositions may help prevent negative patient outcomes. 32 Specific to mental health clinical education, students have reported that reflective journaling provided them opportunities for selfreflection, leading to increased understanding of patients' perspectives and mental health competency.…”
Section: Sp Encountermentioning
confidence: 99%